Mechanical properties and fracture mechanism of high-strength FGH4097 superalloys prepared by hot oscillatory pressing - Pengfei Li; Hong Huang; Wenzhuo Du; Yan Fan; ruiming Yin; shangdong Hou; Liwen Sheng (Journal of Materials Research and Technology)
A powder metallurgy (PM) nickel-based superalloy of FGH4097 with Φ160mm × 90 mm was prepared by hot oscillatory pressing (HOP) method and heat treatment process. The mechanical properties and fracture mechanism of FGH4097 superalloys at room temperature and 650 °C were studied. The density was 8.36 g/cm3, and the highest tensile strength and elongation at room temperature reached 1483 MPa and 26%, respectively. At 650 °C, the highest tensile strength and elongation reached 1331 MPa and 28%, respectively. At 650 °C, after 24000 cycles of high cycle fatigue and 100 h of endurance strength, it did not break. The mechanical properties of FGH4097 superalloys prepared by hot oscillating pressing sintering are comparable to those of “plasma rotating electrode processing (PREP) and hot isostatic pressing (HIP)” technology. The fracture surface of FGH4097 superalloys at room temperature and 650 °C exhibits distinct morphological features of fiber zone, radiation zone, and shear lip zone. The average grain size was 48.92 μm, and approximately 320 nm of γ′ phase and (Nb, Ti) C phase were precipitated. The prior particle boundaries (PPBs) effect of primary γ′ phase and carbide phase at the grain boundaries is suppressed. The combined effect of grain boundary strengthening, solid solution strengthening, precipitation strengthening, and stacking fault strengthening enhances the yield strength and ductility. This work not only reduce the production cost and short the manufacturing cycle of powder superalloys, but also promote the application of powder superalloys in high temperature field.